1997
DOI: 10.1182/blood.v89.3.929
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-7 Receptor by Lineage-Negative Human Bone Marrow Progenitors With Enhanced Lymphoid Proliferative Potential and B-Lineage Differentiation Capacity

Abstract: Relatively little is known about the relationship of lymphoid-associated gene expression to the proliferation and differentiation potential of early human bone marrow lymphoid progenitors. Surface expression of interleukin-7 (IL-7) receptor-α (IL-7Rα), a component of the high-affinity receptor for the lymphoid precursor growth factor IL-7, defined a CD34+ progenitor subset lacking the CD19+ pro-B phenotype but demonstrating markedly enhanced lymphoid clonogenic capacity and the ability to differentiate into pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(25 citation statements)
references
References 45 publications
2
20
0
1
Order By: Relevance
“…There are also some notable differences in characteristics of cells that express the enzyme. For example, the TdT + cells in humans are CD34 + and few are c-kit + (43). This is in contrast to the mouse where the majority of TdT + cells are c-kit lo and CD34 -.…”
Section: Comparable Stages In Human Bone Marrowmentioning
confidence: 90%
See 1 more Smart Citation
“…There are also some notable differences in characteristics of cells that express the enzyme. For example, the TdT + cells in humans are CD34 + and few are c-kit + (43). This is in contrast to the mouse where the majority of TdT + cells are c-kit lo and CD34 -.…”
Section: Comparable Stages In Human Bone Marrowmentioning
confidence: 90%
“…CD45RA appears prior to CD19 in mouse and man. However, most human TdT + cells are CD45RA + while a majority of murine TdT + precursors are CD45RA - (8,10,43).…”
Section: Comparable Stages In Human Bone Marrowmentioning
confidence: 99%
“…Does the incomplete reconstitution of peripheral B cell numbers in the double-mutant mice reflect species-specific differences in the IL-7 dependence of the B cell development? While some data support an important role for IL-7 during human B cell develoment [24][25][26], others demonstrate that IL-7independent B cell development can occur in man [27]. The fact that SCIDX1 patients have normal numbers of B cells supports the latter finding, but whether IL-7independent B cell development in man is a major or minor developmental pathway under normal conditions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ryan et al [22] reported that progenitor B cells did not express c-Kit. We also detected G-CSFR, but not c-Kit, on the progenitor B cells by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%